f(x) = -6x- 1 and g(x) = -(5+4x)

What is the solution for (f - g) (x)?

What is the solution for (f - g) (x)?

f(x) = -6x- 1 and g(x) = -(5+4x)

What is the solution for (f - g) (x)?

What is the solution for (f - g) (x)?

Tutors, please sign in to answer this question.

Chevy Chase, MD

(f-g) (x) = f(x) - g(x)

So (f-g) (x) = (-6x-1) - [-(5+4x)] = -6x-1+5+4x = -2x+4

Amaan M.

Math/Economics Teacher

New York, NY

5.0
(68 ratings)

Alex C.

Harvard/MIT Finance and Statistics Tutor

Fort Lee, NJ

5.0
(263 ratings)

Andrea R.

Ph.D. Tutor: K-9 Reading, Math, Writing, Test Prep, Special Needs

Wyckoff, NJ

5.0
(409 ratings)

- Math Help 5028
- Algebra 4732
- Math Word Problem 4062
- Calculus 2086
- Word Problem 4847
- Algebra 2 3242
- Algebra 1 3853
- Math Problem 948
- Math Help For College 1339
- Math Equations 930